Spectroscopic Investigations of High‐Nitrogen Compounds for Near‐Infrared Illuminants. Issue 2 (28th October 2013) - Fischer, Niko; Feller, Michael; Klapötke, Thomas M.; Kowalewski, Markus; Scheutzow, Susanne; Stierstorfer, Jörg
Abstract Alkaline metal salts are widely used in pyrotechnic formulations. For NIR pyrotechnics, potassium, and cesium nitrate are mainly used as oxidizers and infrared emitters. Herein, new NIR illuminant formulations were tested using several potassium and cesium salts of high‐nitrogen compounds such as tetrazole and triazole derivatives. The research of new formulations comprises the evaluation of sensitivity data and radiometric measurements of new formulations. It was further investigated whether the IR emission can be improved using different nitrogen releasing agents like aminotetrazole or diethylene triamine trinitrate (DETT) as hexamethylenetetramine replacements.